Exfoliation methods for compositional and electronic characterization of interfacial Mo(Sex, Sy) in Cu(In, Ga)(Se, S)2 solar cells by X‐ray and UV photoelectron spectroscopy. (1st March 2022) - Lange, Stefan; Giesl, Florian; Naumann, Volker; Hagendorf, Christian; Eraerds, Patrick
Abstract : Mo(Se x S y ) is a transition metal dichalcogenide typically applied as a back contact interlayer in Cu(In, Ga)(Se, S)2 (CIGSSe) solar cells. Band alignment at the buried Mo/CIGSSe junction mediated by Mo(Se x S y ) is important for current transport and enables quasi‐ohmic behavior between the CIGSSe absorber and the Mo back electrode. Furthermore, the S/(Se + S) ratio is a crucial parameter that determines the height of the valence band offset at the CIGSSe/Mo(Se x S y ) interface. Because the interlayer is formed during rapid thermal processing, an MoSe2 or MoS2 thin film grown on free substrate surfaces will not be representative for a realistic solar cell device. Thus, for fundamental thin‐film material analysis, as well as functional characterization and modeling, appropriate preparation and analytical techniques are required in order to prevent artifacts. In principal, the weak van der Waals forces between two‐dimensional stacked Mo(Se x S y ) sheets allow the implementation of exfoliation procedures to generate free Mo(Se x S y ) surfaces out of CIGSSe solar cell layer stacks. In this article, two different exfoliation‐based Mo(Se x, S y ) preparation methods are investigated and evaluated with respect to subsequent surface analytical characterization by X‐ray and ultraviolet photoelectron spectroscopy. A special focus is laid on an artifact‐free characterization of chemical and electronical properties of the exposed layers for a number of samples. In a first instance, the compositional Se/S and (Se + S)/Mo ratios at the surface are quantitatively analyzed on the basis of dedicated peak‐fitting routines. Artifacts from carbonaceous contamination due to different exfoliation glues can be prevented through a detailed comparative analysis of carbon 1s and KLL Auger peaks. Furthermore, a significant surface band bending is observed that can be reduced by low‐energy Ar ion in situ sputtering. A simple model for the sputter removal of a charged surface layer is presented, which allows to approximately calculate the absolute valence band maximum (VBM) positions required for band alignment and numerical device simulations. The presented exfoliation surface analysis methodology is important for the whole CIGS(Se) solar cell community and may be of general interest for emerging applications of further 2D transition metal dichalcogenides as well.